PHYSICS OF BLOODSTAIN PATTERN ANALYSIS - Afdhila, Zakia (Universitas Airlangga, 2025)
Bloodstain patterns are one of the pieces of evidence that can be found at the scene. Bloodstain pattern analysis is carried out to help reconstruct the events or occurrences that caused the formation of the pattern. Analysis is based on a combination of physics, biology and mathematics. Factors that influence the formation of bloodstain patterns are: surface tension and viscosity, drag and gravity and their influence on speed, and the shape of bloodstains when falling. In addition, surface conditions can affect the pattern of blood produced. Determining the area of